Exon repetition in mRNA - Frantz, Simon A. (The National Academy of Sciences, 1999)
The production of different transcripts (transcript heterogeneity) is a feature of many genes that may result in phenotypic variation. Several mechanisms, that occur at both the DNA and RNA level have been shown to contribute to this transcript heterogeneity in mammals, all of which involve either the rearrangement of sequences within a genome or the use of alternative signals in linear, contiguous DNA or RNA. Here we describe tissue-specific repetition of selective exons in transcripts of a rat gene (SA) with a normal exon–intron organization. We conclude that nonlinear mRNA processing can generate tissue-specific transcripts.